Highly selective and reversible NO2 gas sensor using vertically aligned MoS2 flake networks. (19th September 2018) - Kumar, Rahul; Kulriya, Pawan K; Mishra, Monu; Singh, Fouran; Gupta, Govind; Kumar, Mahesh
Abstract: We demonstrate a highly selective and reversible NO2 resistive gas sensor using vertically aligned MoS2 (VA-MoS2 ) flake networks. We synthesized horizontally and vertically aligned MoS2 flakes on SiO2 /Si substrate using a kinetically controlled rapid growth CVD process. Uniformly interconnected MoS2 flakes and their orientation were confirmed by scanning electron microscopy, x-ray diffraction, Raman spectroscopy and x-ray photoelectron spectroscopy. The VA-MoS2 gas sensor showed two times higher response to NO2 compared to horizontally aligned MoS2 at room temperature. Moreover, the sensors exhibited a dramatically improved complete recovery upon NO2 exposure at its low optimum operating temperatures (100 °C). In addition, the sensing performance of the sensors was investigated with exposure to various gases such as NH3, CO2, H2, CH4 and H2 S. It was observed that high response to gas directly correlates with the strong interaction of gas molecules on edge sites of the VA-MoS2 . The VA-MoS2 gas sensor exhibited high response with good reversibility and selectivity towards NO2 as a result of the high aspect ratio as well as high adsorption energy on exposed edge sites.